Beyond Juvenile Mental Narrative: Social Justice and Redemptive Vision in Wole Soyinka’s Autobiography, Ake: The Years of Childhood - Kekeghe, Stephen Ese; Oghounu, Christy Ese (NIU Journal of Humanities, 2024)
In Nigerian literary expressions, including fictionalized and auto/biographical narratives, there is a strong moralizing or didactic undertone which attests to the mores and values that define the African cultural space. As a writer-activist, Wole Soyinka’s literary productions have often foregrounded his quest for social justice in his immediate and larger community. This revolutionary commitment permeates his writings, including autobiographies. This article examines Soyinka’s quest for justice and social reclamation in his childhood memoir, Ake: The Years of Childhood. The text is purposively selected and subjected to the tools of qualitative literary analysis, relying on the tenets of Postcolonial theory. The researchers argue that Soyinka’s socialist consciousness and commitments manifest through the young Wole in Ake, thereby exhibiting the mental qualities of an adult. Keywords: Literary autobiography; Postcolonialism; Wole Soyinka; Ake